Eco-conscious TLC assay for dual psoriasis drugs in plasma: a green analytical approach - Maimana A. Magdy; Basma H. Anwar; Nehal F. Farid; Nessreen S. Abdelhamid (BMC Chemistry)
Abstract Psoriasis is one of the dermatological autoimmune diseases that involve cracking, redness, bleeding and inflammation on the surface of the skin. Sulfasalazine (SUL) is an immunity suppressing and anti-phlogistic drug. Pentoxifylline (PTN) is an immunosuppressant and vasodilator. So, the two drugs are co-administered together in the treatment protocol for psoriasis. No chromatographic analytical method was developed in the literature for the quantitative determination of SUL and PTN in their binary mixture and spiked human plasma. So, this work’s goal is to establish an environmentally friendly and selective TLC method for quantitative assay of sulfasalazine and pentoxifylline in their common mixture and spiked human plasma samples. The separation was successfully obtained using a developing system consisting of ethanol: ethyl acetate (7: 3, v/v) and 270 nm as UV scanning wavelength. Paracetamol was chosen as an internal standard to correct sampling minute variations. The obtained retardation factor values were 0.02, 0.43, 0.68 and 0.8 for plasma, pentoxifylline, sulfasalazine and paracetamol, in the same order. The resulting LLOQ for SUL and PTN were 0.3 and 0.2 µg/band, respectively. Three environmental friendliness assessment tools including analytical greenness metric approach (AGREE), eco-scale assessments, and green analytical procedure index (GAPI) were applied to evaluate the environmental safety characters of the suggested method. Validation parameters were within the accepted ranges when checked according to US-FDA guidelines to for bioanalytical method validation.